Pemanfaatan Limbah Serbuk Kayu Sengon sebagai Filler pada Campuran Beton - Karimah, Rofikatul; Darmawan, Azhar Adi; Amal, Andi Syaiful (Universitas Batanghari Jambi, 2025)
This study aims to reduce the environmental impact caused by the disposal of sawdust waste by using it as a filler in concrete mixtures, which acts as a filler for concrete pores which is expected to contribute to increasing the strength of concrete. This study focuses on the type of sawdust from waste from sengon (albazia) sawmills obtained from sengon wood craftsmen in Jatimulyo Village, Lowokwaru District, Malang City. The method used is an experiment that begins with a series of tests on concrete-forming materials before making test objects such as sand, gravel and sawdust waste. Then, test objects are made with varying amounts of sengon wood fiber added. The research results obtained an optimum value for the addition of 0.75% sengon wood fiber with a compressive strength of fc'= 20.65 Mpa, while for the concrete density test with the addition of sengon wood powder waste and without the addition of sengon wood powder waste did not affect the concrete density where the concrete density still meets the requirements set by SNI 03-2847-2019 which has a reference range for normal concrete density of 2200 kg/m3 - 2500 kg/m3.